The effects of the centrifugation speed on the survival of autogenous fat grafts in a rat model. Issue 3 (3rd May 2016) - Bozkurt, Mehmet; Kapı, Emin; Şirinoğlu, Hakan; Güvercin, Emre; Filinte, Gaye Taylan; Filinte, Deniz
Abstract: Purpose The most important problem in fat transplantation is the durability, which is closely associated with the applied technique. This study includes the comparison of different centrifugation speeds on the survival of autogenous fat grafts in rats. Materials and methods Forty-nine Sprague-Dawley rats were divided into seven groups and the left inguinal fat pad was extracted and re-implanted under the scalp after performing appropriate preparation processes. In the first group the fatty tissue was re-implanted in en-bloc fashion and in the second group it was re-implanted after trimming. After trimming, centrifugation with a G-force of 111.8 (1000 rpm) was performed in the third group, 447.2 (2000 rpm) in the fourth group, 1006.2 (3000 rpm) in the fifth group, 1788.8 (4000 rpm) in the sixth group, and 2795 (5000 rpm) in the seventh group for 4 minutes. The fat grafts were taken after 3 months and histopathological and statistical evaluations were performed. Results The rate of viable fat grafts was significantly higher in the 4th and 5th groups comparing to the first three groups. Total weight and volume amounts of the 4th and 5th groups were also significantly higher comparing to the first three groups. Conclusion Maximal long-term durability and fat cell viability results were obtained in the groups with 2000 rpm or 447.2 G-force/4 minutes and 3000 rpm or 1006.2 G-force/4 minutes centrifugation speed, indicating that 4 minutes centrifugation with an average G-force of 698.75 or 2500 rpm provides the best results for the survival of autogenous fat grafts.